2013
DOI: 10.1166/jnn.2013.6010
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Magnetic Properties of Multilayer Polymer Structures with Nano Inclusions as Prepared by Selective Laser Sintering

Abstract: Selective laser sintering (SLS) was used to prepare porous polymer nanocomposites comprising of a polycarbonate (PC) matrix doped with 30-50 wt% nano Ni or/and 10-30 wt% nano Cu. The electrical conductivity was measured at f = 1 MHz, bias dc voltage 40 V, and 300-400 K. Magnetic measurements were carried out at r.t. in magnetic fields of up to 10 kOe. Temperature dependence of electrophysical properties was studied for 3D samples derived from PC-Cu powders. Magnetic properties were measured for alternating fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The optic facility was used with the beam focal length of 147 mm and shift of 25 mm from the bottleneck. The layer-by-layer laser sintering process was performed in a specially designed camera in the air which was described earlier 9 . Figure 2(a, b) shows how each of these components was arranged in our system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optic facility was used with the beam focal length of 147 mm and shift of 25 mm from the bottleneck. The layer-by-layer laser sintering process was performed in a specially designed camera in the air which was described earlier 9 . Figure 2(a, b) shows how each of these components was arranged in our system.…”
Section: Methodsmentioning
confidence: 99%
“…As it is known, sintering is a thermally activated process that is accompanied by coagulation of the NPs into micro-sized conglomerates. Stabilization of the NPs in a liquid solution makes possible to arrange a desired distribution of the NPs in organic polymer 6,9 and thus to protect them from oxidation and even to design functionally graded (FG) structures. To overcome this limitation alternative "low temperature" laser sintering approach has to be utilized.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for the first time the selective bacterial test systems for the analysis of drinking water quality were researched and developed, mechanisms of diagnosing pancreatitis were studied with the aid of biosensors applied to the inkjet 3D printing substrate. Just that very method was used to obtain noninvasive high-sensitive biochips estimating the content of hydrogen peroxide and glucose, as well as to design colorimetric sensors aimed to detect neurotoxins and pesticides [5,10]. However, the use of the inkjet 3D printing mechanism for bioengineering basically reduced to finding of new approaches to the biomolecules fixation into porous matrices that ensure a stable trapped substance for a long period of time after its deposition on the substrate and drying.…”
Section: Inkjet 3d Printing Of Optical Nanostructuresmentioning
confidence: 99%
“…Functionally graded 3D parts with alternating ferromagnetic Ni-PC and nonmagnetic Cu-PC layers [5] exhibited hysteresis phenomena that can probably be used in microelectromechanical systems (MEMS)-nanoelectromechanical systems (NEMS) applications [6] also, where the time response must depend on the relaxation rate. The synthesized nanocomposites with high porosity and large-specific surface could also find their application in catalysis, lab-on-chips, drug delivery systems, and 3D crystalline structures for hydrogen storage devices [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the thickness of the superconducting surface layer is independent of the particles size and is about 6 nm (approximately 30 atomic layers); however, in case of smaller particles, the anomalous diamagnetism disappears completely at room temperature. Evaluation of the second critical field for the superconductivity vanishing indicates the expected value of at least 15 T at 300 K. Further consolidation of powder of these particles with the abovementioned magnetic behavior peculiarities was also studied applying the method of laser sintering under conditions ensuring the preservation of the superconductivity in the individual nanoparticles [194].…”
Section: Fig 17mentioning
confidence: 99%